Assessment of the molecular composition of humic acid as an indicator of soil carbon levels by ultra-high-resolution mass spectrometric analysis. (May 2020) - Jiménez-González, Marco A.; Almendros, Gonzalo; Waggoner, Derek C.; Álvarez, Ana M.; Hatcher, Patrick G.
Graphical abstract: Highlights: A relationship exists between SOC content and the composition of soil HAs. Unsaturated lipid and lignin structures prevail in high SOC content scenarios. Saturated lipid prevails in low SOC content scenarios. Humic acid structure keeps information on soil properties as SOC content. The SOC can be predicted from the molecular composition of HAs. Abstract: Long-term stabilization of soil organic matter (SOM) plays an important role in the carbon cycle. Hence, understanding biogeochemical mechanisms of soil C sequestration is crucial to control its release to the atmosphere. This study aims at investigating the biogeochemical mechanisms of soil C sequestration. An exploratory assessment was carried out on the information about the soil C levels provided by the molecular composition of humic acids (HAs) analyzed by electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS). Significant PLS forecasting model for total soil C was obtained using as descriptors the 131 compounds in common in all the HAs detected by FTICR-MS, and its variable importance for projection (VIP) was plotted in the space defined by their atomic ratios using van Krevelen diagrams. The results indicated that significant relationship exists between the HAs molecular composition and the soil organic C levels. The VIP values for the different groups of compounds illustrate how HA contains information about the amounts of C stored in the soil: the HAs in the soils with high levels of organic C have significantly ( P  < 0.1) higher proportions of unsaturated lipid and lignin-derived compounds; on the other side, low soil organic C levels are associated to HAs with comparatively high proportions of saturated lipid compounds.